Corrective justice - Weinrib, Ernest Joseph (Oxford : Oxford University Press, 2012)
Private law governs our most pervasive relationships: the wrongs we do one another, the contracts we make and break, and the property we own. This text analyses the deepest questions about the law's foundations, showing how a distinctive notion of justice, 'corrective justice', describes the morality intrinsic to private law.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Civil law -- Philosophy